Seismic fragility functions for Portuguese RC precast buildings - Sousa, R. (2020)
Fragility functions are fundamental for the assessment of seismic safety of structures or the loss assessment of a portfolio of assets. The present paper describes a procedure to derive fragility functions representative of Portuguese reinforced concrete precast buildings. This goal was achieved following an analytical methodology considering the result of hundreds of nonlinear static analyses, whose building models reflect both mechanical and geometrical characteristics of the Portuguese industrial building stock. Considering the specificities of this typology, and in particular the connections between the structural members, a recently developed macro-element was employed, which enables the explicit simulation of friction and dowel mechanisms. The fragility analyses considered both structural and non-structural limit states, and the findings indicate a poor seismic performance, even under low seismic demand.